OTUB1 Promotes Progression and Proliferation of Prostate Cancer via Deubiquitinating and Stabling Cyclin E1 - Liao, Yihao; Wu, Ning; Wang, Keke; Wang, Miaomiao; Wang, Youzhi; Gao, Jie; Zhong, Boqiang; Ma, Fuling; Wu, Yudong; Jiang, Ning (Frontiers in Cell and Developmental Biology, 2021)
Background: Prostate cancer (PCa) is currently the most common cancer among males worldwide. It has been reported that OTUB1 plays a critical role in a variety of tumors and is strongly related to tumor proliferation, migration, and clinical prognosis. The aim of this research is to investigate the regulatory effect of OTUB1 on PCa proliferation and the underlying mechanism. Methods: Using the TCGA database, we identified that OTUB1 was up-regulated in PCa, and observed severe functional changes in PC3 and C4-2 cells through overexpression or knock down OTUB1. Heterotopic tumors were implanted subcutaneously in nude mice and IHC staining was performed on tumor tissues. The relationship between OTUB1 and cyclin E1 was identified via Western blotting and immunoprecipitations assays. Results: We found that the expression of OTUB1 in PCa was significantly higher than that in Benign Prostatic Hyperplasia (BPH). Overexpression OTUB1 obviously promoted the proliferation and migration of PC3 and C4-2 cells via mediating the deubiquitinated Cyclin E1, while OTUB1 knockout has the opposite effect. The nude mice experiment further explained the above conclusions. We finally determined that OTUB1 promotes the proliferation and progression of PCa via deubiquitinating and stabling Cyclin E1. Conclusions: Our findings reveal the critical role of OTUB1 in PCa, and OTUB1 promotes the proliferation and progression of PCa via deubiquitinating and stabilizing Cyclin E1. Blocking OTUB1/Cyclin E1 axis or applying RO-3306 could significantly repress the occurrence and development of PCa. OTUB1/Cyclin E1 axis might provide a new and potential therapeutic target for PCa.